Corporate governance structures, institutional pressures and voluntary disclosure in Malaysia / Roshayani Arshad - Arshad, Roshayani (2009)
Detailed disclosure about managers' activities in relation to company's performance and future growth prospects to investors and other stakeholders have been subjected to calls for transparency as part of the corporate governance movement. Managers face substantial pressures to increase corporate disclosure as a matter of good corporate governance practice or otherwise risk potential loss of legitimacy regarding their activities from the perspectives of investors and other stakeholders. In such situation, can managers voluntary disclosure strategy reveals credible information as monitoring mechanism to investors. Hence, this study examines the competing effects of corporate governance structures and institutional pressures on management voluntary disclosure decisions, in terms of both the extent and credibility of the information disclosed.